2015
DOI: 10.1007/s00726-015-2039-5
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase 2 up-regulation is associated with RANKL/OPG pathway in cultured HPDL cells and THP-1-differentiated macrophages

Abstract: Recent evidence emphasized that transglutaminase 2 (TG2), a protein cross-linking enzyme, may play a role in the early phase of inflammation. High levels of TG2 have been associated with the constitutive activation of nuclear factor-kappa B (NF-κB) that is considered the main regulator of inflammation. In this context, the receptor activator of NF-kappa B ligand (RANKL) and receptor activator of NF-κB have extensive functions in the regulation of cytokine secretion associated with different pathological condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…Periodontal disease, 3 as well as widening of periodontal ligament spaces and abnormalities in periodontal microcirculation, have been reported as a frequent finding as part of the global fibrosing aspects of SSc. 4 Recently, in accord with the authors' results, we reported a detectable prevalence of symptoms and signs of dysfunction of TMJs and self-reported symptoms in SSc patients (limited and diffuse) compared with healthy subjects. 5 Notably, our study primarily demonstrated in the SSc group an association between TMJ symptoms with MRSS and the mean duration of SSc.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Periodontal disease, 3 as well as widening of periodontal ligament spaces and abnormalities in periodontal microcirculation, have been reported as a frequent finding as part of the global fibrosing aspects of SSc. 4 Recently, in accord with the authors' results, we reported a detectable prevalence of symptoms and signs of dysfunction of TMJs and self-reported symptoms in SSc patients (limited and diffuse) compared with healthy subjects. 5 Notably, our study primarily demonstrated in the SSc group an association between TMJ symptoms with MRSS and the mean duration of SSc.…”
supporting
confidence: 85%
“…SSc is a multisystem disorder of the connective tissue of the skin and underlying tissues that can have significant adverse effects on the health of the mouth. Periodontal disease, 3 as well as widening of periodontal ligament spaces and abnormalities in periodontal microcirculation, have been reported as a frequent finding as part of the global fibrosing aspects of SSc 4 …”
mentioning
confidence: 99%
“…Etiologically, inflammatory cytokines including matrix metalloproteinases (MMPs), IL-1β, IL-6, TNF-α, nitric oxide, and prostaglandin E2 seem to be involved in the process of IVDD leading to loss of cells and ECM [11,12]. Among these inflammatory cytokines, TNF-α is known as a pro-inflammatory cytokine for NPCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to causing increased matrix deposition through activation of TGF‐β1, TGM‐2 cross‐linking of ECM results in reduction in matrix turnover leading to net deposition and accumulation 45 , 46 . Cytokines and growth factors secreted during early phases of cell injury regulate TGM‐2 expression 47 that has been shown to play a relevant role in inflammatory states 47 , 48 . In the present study, both GCF and plasma levels of TGM‐2 were elevated in CsA GO+ group compared with G and H groups.…”
Section: Discussionmentioning
confidence: 99%